Challenges and Barriers to Implementing Multicultural Counseling in Schools - Amelia Juloma Mboes; Lidia Jelaus; Priska Diana Lisa (CERDAS AKADEMIKA NUSANTARA, 2026)
This study aims to examine the various challenges faced in the implementation of multicultural counseling in school settings. The method used was a Systematic Literature Review (SLR), which analyzed five articles from national journals selected according to predetermined criteria. The data were analyzed using a qualitative descriptive approach to identify the nature of these challenges and potential solutions for implementing multicultural counseling. The results of the study indicate that multicultural counseling services still face various obstacles, including limitations in counselors’ competence and cultural sensitivity, weak intercultural communication skills, the emergence of stereotypes and prejudices, a tendency toward counselor encapsulation, and differences in language, dialect, values, and cultural norms between counselors and clients. Additionally, students also experience difficulties adapting, barriers in interpersonal communication, social anxiety, and low self-confidence due to cultural differences. Other barriers are related to institutional factors, such as the lack of a systematically structured multicultural counseling program, limited understanding among guidance counselors regarding cultural diversity, and minimal support from schools, families, and the community. On the other hand, the development of globalization and technology has further expanded the cultural diversity of students, thereby increasing the complexity of counseling services. Research findings indicate that the effectiveness